ADVPlayer Web: Accessibility in Videos for People with Visual Impairments via Synthesized Audio Description – A Requirements Evaluation (Revista Brasileira Multidisciplinar, 2026)
Audiodescription is essential for making audiovisual content accessible to visually impaired individuals, converting visual information into audio descriptions. Typically done by human narrators, audiodescription can be complemented by virtual technologies with synthesized voice. This study evaluated the accessibility of ADVPlayer Web, a software for playing videos with virtual audiodescription. Using automatic tools like TAW, Accessi, and Google PageSpeed, the strengths and weaknesses of ADVPlayer were identified. The software achieved high performance and accessibility scores (above 90/100) but showed areas for improvement, such as replacing links with buttons, adjusting titles and labels, and correcting color contrast. The study emphasizes the importance of investing in technological solutions to promote digital inclusion, ensuring that everyone can fully enjoy audiovisual content.
Keywords: Audiodescription; Accessibility; Visual impairment; ADVPlayer; Assistive Technology